Development of E-Dictionary Media in Food Science Courses - Fridiarty, Lelly; Waruwu, Mawadda Azizah Sari; Nasution, Nadrah Afiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Technological advances require lecturers to be more active in developing learning media so that they can help students participate more actively in learning independently. This research aims to develop e-dictionary-based media in food science courses. The media development model adopts the Brog and Gall procedure. Media validation is carried out by material and media experts. The results of the needs analysis indicate that e-dictionary-based media is highly needed in food science courses. The material expert validation percentage indicates 84% in the good category. The media validation result is 88% in the very good category. The result of limited trials conducted on students is 87% in the very good category. The result of the field trials is 88.25% in the very good category. As a result, it can be concluded that e-dictionary-based learning media is suitable for use in food science courses, especially in the introduction of cooking herbs and spices. With e-dictionary-based media, it is expected that it can become a learning innovation that collaborates with Android cell phone technology.